2018
DOI: 10.1038/s41564-018-0160-4
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus neoformans sexual reproduction is controlled by a quorum sensing peptide

Abstract: Bacterial quorum sensing is a well-characterized communication system that governs a large variety of collective behaviours. By comparison, quorum sensing regulation in eukaryotic microbes remains poorly understood, especially its functional role in eukaryote-specific behaviours, such as sexual reproduction. Cryptococcus neoformans is a prevalent fungal pathogen that has two defined sexual cycles (bisexual and unisexual) and is a model organism for studying sexual reproduction in fungi. Here, we show that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 44 publications
2
64
0
Order By: Relevance
“…On the other hand, Ustilago maydis Rep1 protein is also cleaved by kexin-protease and has a structural role in the fungal cell wall (Wödsten et al, 1996;Teertstra et al, 2006). An 11 amino acid long peptide processed by KEX2 in Cryptococcus neoformans is required for virulence and to activate the sexual program (Homer et al, 2016;Tian et al, 2018). Since MiSSP8-RNAi lines are not impaired in hyphal growth or fungal cell-wall sensitivity, it is unlikely that MiSSP8 or its derived peptides are involved in fungal cell wall structure.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Ustilago maydis Rep1 protein is also cleaved by kexin-protease and has a structural role in the fungal cell wall (Wödsten et al, 1996;Teertstra et al, 2006). An 11 amino acid long peptide processed by KEX2 in Cryptococcus neoformans is required for virulence and to activate the sexual program (Homer et al, 2016;Tian et al, 2018). Since MiSSP8-RNAi lines are not impaired in hyphal growth or fungal cell-wall sensitivity, it is unlikely that MiSSP8 or its derived peptides are involved in fungal cell wall structure.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been indicated that the presence of copper in media has a positive effect on mating. Additionally, use of glucosamine as the sole carbon source in nutrient-rich media as well as the presence of quorum-sensing peptides has been shown to induce filamentation in Cryptococcus in recent studies (Kent, Ortiz-Bermudez, Giles, & Hull, 2008;Tian et al, 2018;Xu et al, 2017;Xue, Tada, Dong, & Heitman, 2007).…”
Section: Mating Mediummentioning
confidence: 99%
“…Several fungal peptides are produced from KEX2-processed precursor proteins 504 Ustilago maydis Rep1 protein is also cleaved by kexin-protease and has a structural role in the 507 fungal cell wall (Wösten et al, 1996;Teertstra et al, 2006). A 11 amino acid long peptide 508 processed by KEX2 in Cryptococcus neoformans is required for virulence and to activate the 509 sexual program (Homer et al, 2016;Tian et al, 2018). Since MiSSP8-RNAi lines are not 510 impaired in hyphal growth or fungal cell-wall sensitivity, it is unlikely that MiSSP8 or its 511 derived peptides are involved in fungal cell wall structure.…”
Section: Aggregation 460mentioning
confidence: 99%